A comprehensive experimental study on temperature-dependent performance of lithium-ion battery. (25th July 2019) - Lu, Z.; Yu, X.L.; Wei, L.C.; Cao, F.; Zhang, L.Y.; Meng, X.Z.; Jin, L.W.
Highlights: Two different thermal conditions are established to explore the lithium-ion battery performance. Battery pack without BTMS intervention may have an excellent discharging performance. Battery charging performance is independent on the charging temperature ranged from 20 °C to 40 °C. The irreversible heat can be regarded as the sole heat source term to simplify battery thermal model. Abstract: The relationship between lithium-ion battery performance and operating temperature is of significance in designing battery thermal management system (BTMS). In this study, two different thermal conditions, namely constant temperature condition and near-adiabatic condition are established to explore charging/discharging characteristics and heat generation behaviors of the lithium-ion battery with Li(Nix Coy Alz )O2 cathode. The objective of creating near-adiabatic condition is to discover the effect of the heat generated by battery itself on charging/discharging characteristics. The experimental results show that the battery charging characteristics are nearly independent on the charging temperature ranged from 20 °C to 40 °C, while the battery charging/discharging performance degrade dramatically for the battery temperature lower than 20 °C. Although the heat generated by battery itself may accelerate battery degradation during cycling due to the adverse effect of excessive temperature, however it improves the discharging performance in a suitable temperature range. This implies that a battery pack may have an excellent discharging performance without BTMS intervention at a moderate discharging rate (e.g., 0.5 C). The irreversible heat could be regarded as the sole heat source term to simplify the battery thermal model due to negligible thermal effect caused by the small amount of reversible heat when the battery is discharged at higher discharging rates.